Efficacy and safety of valsartan/amlodipine single-pill combination in patients with essential hypertension (PEAK LOW) - Pınar Kızılırmak; İdilhan Ar; Barış İlerigelen (KARE Publishing, 2014)
Objectives: This study evaluated the efficacy as well as the safety and tolerability profile of low-dose valsartan/amlodipine (Val/Amlo) single-pill combination (SPC) (160/5 mg) in patients with essential hypertension in Turkey. Study design: Adult patients with essential hypertension [systolic blood pressure (SBP) >140 mmHg and/or diastolic blood pressure (DBP) >90 mmHg], who were on low dose Val/Amlo (160/5 mg) SPC before enrollment and gave informed consent, were accepted for this multi-centric observational study performed at 30 sites. The absolute changes in SBP and DBP from baseline were the primary efficacy outcomes. Safety assessments consisted of recording all adverse events. Results: Of 381 patients enrolled, 327 completed the study; 39% were females. The mean age was 57.3+-11.8 years. Median duration of hypertension was 38 months. Both SBP and DBP values showed reductions from 162.6+-16.6 mmHg and 94.0+-13.2 mmHg to 137.6+-14.2 mmHg and 81.9+-9.0 mmHg at 4th week and to 131.6+-11.5 mmHg and 79.7+-7.6 mmHg at 12th week, respectively. The control and response rates at the end of the study were 82.0% and 92.6%, respectively. Twelve patients (3.2%) experienced a total of 12 adverse events; there were no serious adverse events. The most common adverse event was edema (1.3%). Patient compliance was approximately 99%. Conclusion: Low-dose (160/5 mg) Val/Amlo SPC is efficacous and has a good tolerability and safety profile for the management of essential hypertension in Turkey.